Respuesta :

Option A: [tex]$6^{2}+11^{2}=c^{2}$[/tex] is the length of the hypotenuse

Explanation:

From the figure, we can see that the given triangle is a right angled triangle.

Hence, we can determine the length of the hypotenuse using Pythagoras theorem.

Thus, we have,

[tex]$a^{2}+b^{2}=c^{2}$[/tex]

where a and b are the lengths of the sides of the triangle. And c is the hypotenuse.

Thus, substituting the lengths of the sides [tex]a=6[/tex] , [tex]b=11[/tex] and [tex]c=c[/tex] is the hypotenuse.

Substituting these values in the equation, we get,

[tex]$6^{2}+11^{2}=c^{2}$[/tex]

Thus, the length of the hypotenuse is [tex]$6^{2}+11^{2}=c^{2}$[/tex]

ay duud yo answer is A.

ACCESS MORE